The practice of market research : from data to insight - McGivern, Yvonne (Pearson, 2022)
"This fifth edition of The Practice of Market Research: From Data to Insight is most timely; it has been comprehensively updated to reflect the changes in the MRS Advanced Certificate syllabus providing candidates the ideal foundation as they undertake their studies. This book provides a comprehensive, straightforward account of the practice of market and social research that is both easy to read and easy to understand. In preparing this new edition changes have been made to the structure and content to reflect changes in practice and methods and in the ethical, legal and regulatory context in which research operates. The changes are also in response to changes in the syllabus of the MRS Advanced Certificate in Market and Social Research Practice, and in response to customer feedback. In brief, in terms of structure, there are now six sections: Introducing Market and Social Research; Planning and Designing Research; Secondary or Existing Data; Qualitative Research; Quantitative Research; and Bringing It All Together. In terms of content, all chapters have been updated to reflect changes in practice and methods and the language used to describe them, and to provide better explanations of areas that students find difficult. One such area is that covered in Chapter 4 where there is greater explication of the link between understanding the business problem and defining the problem to be researched. Other topics which have significant new content are Chapter 8 on sources of existing data, which includes an expanded section on databases and data warehouses; Chapter 9 on the evaluation of those sources; and Chapter 18 which covers data mining and data analytics in much greater detail than the previous edition".